2018
DOI: 10.2196/mental.7784
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Factors and Barriers to the Use of Emerging Technologies for Suicide Prevention in Europe: Multicountry Exploratory Study

Abstract: BackgroundThis study provides an analysis on the use of emerging technologies for the prevention of suicide in 8 different European countries.ObjectiveThe objective of this study was to analyze the potentiality of using emerging technologies in the area of suicide prevention based on the opinion of different professionals involved in suicide prevention.MethodsOpinions of 3 groups of stakeholders (ie, relevant professionals in suicide field) were gathered using a specifically designed questionnaire to explore d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Our objective is the use of the results of this qualitative research for the creation of a needs study which allows the implementation, in our health area, specific training groups of different professional cadres involved in the approach, treatment and prevention of the suicidal behaviors. This research is part of the European Regions Enforcing Actions Against Suicide (EUREGENAS) European project, which brings together 11 regions with different experiences with the aim to contribute to suicide prevention in Europe [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our objective is the use of the results of this qualitative research for the creation of a needs study which allows the implementation, in our health area, specific training groups of different professional cadres involved in the approach, treatment and prevention of the suicidal behaviors. This research is part of the European Regions Enforcing Actions Against Suicide (EUREGENAS) European project, which brings together 11 regions with different experiences with the aim to contribute to suicide prevention in Europe [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is a topic much debated by researchers who study human behavior in social platforms. In the past, these authors have identified a wide range of "dangerous behaviors", such as: (i) harassing, discriminating (Lawson 2018;Fritz and Gonzales 2018), doxing (Wood et al 2019) and socially disenfranchising vulnerable individuals (Page et al 2018;Linabary and Corple 2019;Mitchell et al 2014;ii) stimulating suicidal tendencies and depressive symptoms among adolescents and young adults (Mitchell et al 2014;Lerman et al 2017;Guan et al 2015;iii) stimulating adolescents and young adults to engage in self-harming behavior (Zhu et al 2016;Pater and Mynatt 2017;Robert et al 2015;iv) stimulating social and aggressive behaviors; (v) stimulating online non-suicidal self-injury; (vi) discussing acts of self-harm and of cybersuicide (Patton et al 2014;Muñoz-Sánchez et al 2018;Khasawneh et al 2020). Such behaviors have been inherited by what we call "dangerous challenges" in TikTok.…”
Section: Related Literaturementioning
confidence: 99%
“…Further analyses have been carried out to assess the role of social platforms with regard to sexual or aggressive behaviors that place youth at risk (Livingstone and Smith 2014). Finally, several researchers have investigated online self-injury and cyber-suicide (Patton et al 2014;Muñoz-Sánchez et al 2018;Khasawneh et al 2020). TikTok removes challenges reported as dangerous and has increased safety controls.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, few studies have examined how social media can influence adolescents and young adults to engage in self-harming behavior [ 24 , 46 , 50 ]. Therefore, interdisciplinary research is beginning to highlight the urgent need to form a cohesive research agenda around digital self-harm [ 50 ], web-based NSSI [ 51 ], the use of social media to discuss deliberate self-harm acts [ 52 , 53 ], and acts of cybersuicide [ 52 , 53 ]. Most of this work, however, is in its early stages, with few drawing upon the developmental aspect of vulnerable adolescents’ social media use.…”
Section: Introductionmentioning
confidence: 99%